Severity-Leniency in Writing Assessment and Its Causal Factors - Azizah, Nur; Suseno, Muchlas; Hayat, Bahrul (KnE Social Sciences, 2020)
Objectivity in a writing assessment is a highly important matter because it determines the validity and reliability of the writing assessment itself. However, subjectivity in the writing assessment is inevitable. Rater subjectivity in the assessment can lead to assessment difference or variability (severity-leniency) eventually reducing the validity and reliability of the assessment. Therefore, the concept of rater variability, severity-leniency, and its causal factors are required to perceive so that efforts to minimize assessment variability, for instance, severity-leniency, can be implemented. The research aimed at providing a brief description of rater variability, namely severity leniency, and the causal factors, namely rater’s background, criteria, method, and assessment scale. The method used in this research was literature study which source was originated from the articles of scientific journals and books related to the research topic, namely rater variability (severity-leniency) and its causal factors. The result of the discussion in this paper showed that the selection of experienced rater, coherent and cohesive assessment criteria, method appropriate to the aim of the research, and brief assessment scale were considered to be able to minimize the variability (severity-leniency) of the rater. Keywords: leniency, rubric, severity, variability, writing assessment